2006
DOI: 10.2353/ajpath.2006.050673
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Inhibition Blunts Nuclear Factor-κB Activation, Reduces Skeletal Muscle Degeneration, and Enhances Muscle Function in mdx Mice

Abstract: Duchenne muscular dystrophy (DMD) is a progressive muscle-wasting disease resulting from lack of the sarcolemmal protein dystrophin. However, the mechanism leading to the final disease status is not fully understood. Several lines of evidence suggest a role for nuclear factor (NF)-B in muscle degeneration as well as regeneration in DMD patients and mdx mice. We investigated the effects of blocking NF-B by inhibition of oxidative stress/lipid peroxidation on the dystrophic process in mdx mice. Five-week-old mdx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 46 publications
6
92
0
2
Order By: Relevance
“…The interplay between ROS and inflammation has also been supported by experiments in which mdx mice have been treated with anti-oxidant drugs, such as vitamin E analogue or N-acetylcysteine (NAC), demonstrating a reduced activation of NF-κB and an amelioration of dystrophic symptoms [105,106,109].…”
Section: Crosstalk Between Oxidative Stress and Inflammatory Responsementioning
confidence: 92%
See 1 more Smart Citation
“…The interplay between ROS and inflammation has also been supported by experiments in which mdx mice have been treated with anti-oxidant drugs, such as vitamin E analogue or N-acetylcysteine (NAC), demonstrating a reduced activation of NF-κB and an amelioration of dystrophic symptoms [105,106,109].…”
Section: Crosstalk Between Oxidative Stress and Inflammatory Responsementioning
confidence: 92%
“…In fact, NF-κB activation is induced by several inflammatory mediators, such as IL-1β, TNFα, and metalloproteinases, all molecules found elevated in DMD [57,[98][99][100][101][102]. Active NF-κB is able to translocate to the nucleus, inducing the expression of genes encoding for cytokines and chemokines, cell adhesion molecules, and matrix metalloproteinases [103][104][105][106][107].…”
Section: Crosstalk Between Oxidative Stress and Inflammatory Responsementioning
confidence: 99%
“…Their study showed that PDTC treatment reduces the activation of NF-κB, muscle necrosis, and fatigue in mdx mice [58]. In addition, in vivo administration of IRFI-042, a potent antioxidant and inhibitor of lipid peroxidation, has been found to block the NF-κB activation and muscle degeneration and provide functional gain in mdx mice [59].…”
Section: Muscular Dystrophymentioning
confidence: 99%
“…Increased forelimb strength normalized to weight and decreased fatigue reported. Reduced serum creatine kinase level also reported, indicating that oxidative stress/lipid peroxidation might be represented as one of the mechanisms activating NF-kappa B and the consequent pathogenetic cascade in mdx mice [18].…”
Section: Discussionmentioning
confidence: 99%